User Perceptions of Academic and Clinical Electronic Medical Records in an Undergraduate Nursing Program - Karen Livesay; Sacha Petersen; Lin Zhao; Kerryn Butler-Henderson; Robab Abdolkhani; Ruby Walter (Bond University, 2023)
_Background_: Electronic Medical Records (EMRs) are a widely used technology within health care. Nursing students require preparation during undergraduate education for the use of EMR. Nursing educators in universities also need to be proficient with EMR. This study reports the experiences and attitudes of nursing students and nurse educators using a simulated Academic Electronic Medical Record (AEMR) system within a nursing degree. _Aim_: To determine nursing student and nursing educator experience with and attitudes towards EMR and AEMR. _Methods_: Nursing students across three years of a Bachelor of Nursing program and nurse educators teaching with an AEMR system completed an online survey. _Results_: Findings from participating nursing students (n=103) revealed a favourable view of the learning and clinical relevance of AEMR (87.5%). Less than half (45.5%) of the surveyed students had been exposed to EMR whilst on clinical placements. In contrast most of the students (38.8%) who had been employed in a health care setting within the previous five years had used an EMR. Nurse educator responses (n=7) showed that most (n=5) had experience with EMR and viewed AEMR as important for student learning, with fewer (n=3) regarding it as an easy system to use. _Conclusion_: The survey revealed that both students and educators were satisfied with AEMR - and that AEMR use was acceptable for use in the University setting. However, the survey shows student exposure to EMR on placement is low. AEMR applications have the potential to bridge the gap in student experience however adequate support and training for academic staff in the use of AEMR is required.